Analisis Defect dengan Metode Fault Tree Analysis dan Failure Mode Effect Analysis - Evan Nugraha; Rini Mulyani Sari (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2019)
There was a phenomenon that occurred in garment companies, namely the existence of defect products in the production process. In the sewing process, defects occurred with an average percentage of 6,67% in the first three months of early 2019. This 6,67% was a percentage of disability that exceeded the company percentage limit of 5%, thus disrupting the production process. The primary purposed of analyzing the factors of product defects was to find out the causes and solutions to the company. The Fault Tree Analysis method was used to find out the root caused of product defects. Three main problems caused product defects, namely 1) untidy stitches, 2) stitches that exceeded the specified size, and 3) straightened stitches. By using the Failure Mode Effect Analysis method, the three problems were caused by human error and the absence of a Standard Operating Procedure in the production process. As a solution to problems in the company, the Risk Priority Number value was used. From this study the result obtained 1 Risk Priority Number value is the proposed improvement.